Ocular Complications of Inflammatory Bowel Disease - Rana Mady; Will Grover; Salim Butrus (The Scientific World Journal)
Though inflammatory bowel disease (IBD) has a specific predilection for the intestinal tract, it is a systemic inflammatory disorder affecting multiple organs, including the eye. Ocular complications directly related to IBD are categorized as primary and secondary. Primary complications are usually temporally associated with IBD exacerbations and tend to resolve with systemic treatment of the intestinal inflammation. These include keratopathy, episcleritis, and scleritis. Secondary complications arise from primary complications. Examples include cataract formation due to treatment with corticosteroids, scleromalacia due to scleritis, and dry eye due to hypovitaminosis A following gut resection. Some ocular manifestations of IBD can lead to significant visual morbidity and temporally associated complications can also be a herald of disease control. Furthermore, ocular manifestations of IBD can occasionally manifest before the usual intestinal manifestations, leading to an earlier diagnosis. Thus, it is important to understand the clinical presentation of possible ocular manifestations in order to initiate appropriate treatment and to help prevent significant visual morbidity.